Skrining Fitokimia Daun Katang – Katang (Ipomoea Pescaprae L. ) - Ayuni Setiawati; Ensu Ensu; Muhammad Said; Yeyen Yeyen; Kristina Tresia Leto (International Forum of Researchers and Lecturers, 2025)
Phytochemistry is a method used to determine the compounds found in plant essence. Phytochemical identification is carried out using chemical substances used in a reaction to determine the collection of secondary metabolite compounds. Indonesia is a country that has various types of medicinal plants, one of which is the leaves of Katang-katang (Ipomoea pes-caprae). Katang-katang is a tropical vine that is easy to find and belongs to the Convolvulaceae family. The utilization of this medicinal plant is one of the alternatives in an effort to treat a disease. Along the road in the sandy beach area, many of these plants are found growing creeping on the edge of the shoreline, this plant has a trumpet-like flower and is known as Katang-katang (Ipomoea pes-caprae). (Ipomoea pescaprae L.). Empirically, people often use katang-katang plants to treat infections in wounds, relieve pain, and as antioxidants. The active compounds of katang-katang as antibacterial are terpenoids, steroids, saponins, tannins and flavonoids. The active compound that plays the most role is thought to be the flavonoid compound content.